Augmented Smart Insoles – Prototyping a Mobile Application: Usage Preferences of Healthcare Professionals and People with Foot Deformities - Resch Stefan; Zoufal Khalid; Akhouaji Imad; Abbou Mohamed-Amin; Schwind Valentin; Völz Diana (Current Directions in Biomedical Engineering, 2023)
The augmentation of smart insoles gained increased interest due to the possibilities in foot-related rehabilitation, medical treatment, and postural risk prevention. As shown by previous work, the technology offers a personalized solution for individual foot morphology and biomechanics, which can monitor the health status and healing process. However, the success of this mobile technology depends on its usability and acceptance by healthcare professionals and patients. Therefore, an exploratory qualitative user study was conducted to investigate the preferences of healthcare professionals and patients regarding augmented smart insoles (ASI) usage. In focus groups, experts and patients explored their needs and suggested potential design solutions. The thematic analysis of the participants’ feedback revealed useful information regarding user interface (UI) designs for the development of a mobile application supporting smart insoles. We found that patients and experts share similar data preferences for a mobile application supporting ASI and that both user groups desired the presence of complete pressure point monitoring, active feedback for posture correction, and personalized training videos for postural risk prevention. However, healthcare professionals expressed concerns regarding the lack of scientific evidence validating the effectiveness of this technology and suggested further research.